Arctic smart specialisation and municipal waste management : Case : North Norway - Teräs, Jukka; Mäenpää, Antti (NORCE, 2024)
This Working Paper introduces and analyses innovation and renewal of municipal waste management in North Norway. We explore how the concept of smart specialisation (S3) could be utilized to enhance R&D and innovation in municipal waste management - a foundational sector which is not typically considered as one of the most innovative sectors of the economy. Our paper reveals that innovation and renewal can be identified within municipal waste management in Arctic peripheral regions, too. Moreover, the paper reports that smart specialisation could be utilized as an additional tool and concept for innovation promotion and R&D collaboration in the Arctic waste management sector under certain conditions. This Working paper is part of the ReCoWaMa (Research collaboration with the Waste Management sector in Troms and Finnmark for improved value creation) project 2023-2025, funded by the RFF Arktis programme.
Keywords: smart specialisation; foundational economy; circular economy; Norway; regional development; fi=Aluetiede|en=Regional Studies|